Who talks about climate, peace and security? A social media analysis to identify key actors - Tucci, Giulia; Carneiro, Bia; Caroli, Giulia; Pacillo, Grazia (2025)
Uncovering key actors within a policy network provides pathways for engagement, consensus-building, partnership development, and understanding the diffusion of knowledge in a given debate. Given the unprecedented scale of the climate emergency, the emerging field of climate security has rapidly gained centrality in academic and policy fora, as well as in the public debate. Yet, a systematic analysis of the main actors engaged in this space is missing. This study draws from digital methods and network analysis techniques to employ a method for identifying relevant actors, focusing on Twitter (now X) from 2014 to 2022, with the objective of spotting the major actors driving public discussions around climate security. The research also demonstrates how institutions can position themselves within such issue networks through a case study of the Consultative Group on International Agriculture Research (CGIAR), a global research-for-development organization that has recently positioned itself in the climate security community. Results reveal that the climate security debate on social media is predominantly institutional, with research bodies and international organizations as central elements. While CGIAR is a relatively new actor, it is already centrally located in the network, maintaining strong connections with other major players, which places it in a strategic position to enhance its influence and reach. Understanding this discursive landscape is crucial for identifying opportunities for effective engagement, partnership, and positioning in such an increasingly salient field of research and practice.